Hierarchical Ru-doped sodium vanadium fluorophosphates hollow microspheres as a cathode of enhanced superior rate capability and ultralong stability for sodium-ion batteries. (January 2017) - Peng, Manhua; Zhang, Dongtang; Zheng, Limin; Wang, Xiayan; Lin, Yue; Xia, Dingguo; Sun, Yugang; Guo, Guangsheng
Abstract: Novel hierarchical Ru-doped Na3 V2 O2 (PO4 )2 F hollow microspheres were synthesized via a low-temperature solvothermal method. The individual unique microspheres were formed from assembly of numerous nanoparticles with diameters of 20–30 nm. When used as a cathode material for sodium-ion batteries (SIBs), the microspheres exhibited superior rate performance with a capacity of 72.6 mAh·g −1 at 10 C. Furthermore, their rate performance could be significantly improved by coating them with a thin conductive RuO2 layer. For instance, high specific capacities of 102.5 mAh g −1 and 44.9 mAh g −1 were achieved at current rates of 20 C and 100 C, respectively. These materials exhibited impressive long-term cycling stability. A reversible capacity of approximately 55.0 mAh g −1 was maintained even after 7500 charge/discharge cycles. Density functional theory (DFT) calculations increased our understanding of how H + facilitates the formation of the hierarchical microsphere superstructure which is beneficial to achieve a good rate capability. Graphical abstract: Novel hierarchical Ru-doped Na3 V2 O2 (PO4 )2 F hollow microspheres with RuO2 coated were successfully synthesized, and exhibited an excellent long-term cycling stability as a cathode material for sodium-ion batteries. Highlights: Na3 V2 O2 (PO4 )2 F (I 4 / mmm ) sodium cathode materials with unique three-dimensional (3D) hierarchical structure overcoming the limitations of nanoparticles was successfully synthesized via a low-temperature solvothermal method. The synthesized hollow microspheres materials of Na3 V2 O2 (PO4 )2 F, Ru-doped Na3 V2 O2 (PO4 )2 F, and Ru-doped Na3 V2 O2 (PO4 )2 F with RuO2 coating used in SIBs exhibited high reversible capacity, long cycle stability, and excellent rate performance. The formation mechanism of ordered hierarchical hollow microspheres controlled by the adsorption of hydrogen was systematically investigated via a series of experimentsand density functional theory (DFT) calculations providing insight to the design and synthesis of new electrode materials with the potential for future applications.